(untitled) (Research, Society and Development, 2022)
In the search for alternative sources to meet the growing demand for energy, wind production has been highlighted due to the great potential for its use in Brazil. Given the magnitude of the foundations of wind turbines, understanding their structural behavior is essential for designing optimized solutions that reduce costs and facilitate the implementation of this technology on a large scale. From this perspective, this article seeks to deepen the studies on the structural behavior of foundations for onshore wind turbines, represented by reinforced concrete pile caps. Computational models were developed using the Finite Element Method (FEM) with the aid of the Ansys Workbench R20 software, considering the contribution of the lateral friction of the pile shaft in the conduction of loads to the ground, as well as the settlement of the piles, through modeling non-linear numerical. The reinforcements of a wind tower foundation were designed and two different mesh organizations were proposed: circular (CR) and orthogonal (OR). From the simulations carried out, the distribution of reactions in the piles and the vertical displacements of the blocks were compared, in different types of soil. It was observed that the reinforced models presented a behavior close to that of rigid blocks, with a tendency towards uniformity of reactions and vertical displacements. At the end, the concrete cracking zones were determined and the tensions in the reinforcement were verified. The results showed that the highest stresses occurred in the models with circular reinforcement (CR), on average 2.06% higher than the OR models. This tendency was associated with the fact that the OR models have proved to be more rigid than the CR models which, being more deformable, impose greater stresses on the reinforcement when flexed by the moment of great magnitude that acts on the foundation.